Are banks effective in the economic recovery from the Arab Spring?. Issue 1 (2nd January 2017) - Haddad, Mahmoud; Hakim, Sam
Abstract : We analyze the role of banks in Bahrain, Egypt, Libya, Tunisia, and Yemen, pre- and post-revolution, and find that the volume of credit they offered to the private sector was neutral to real economic growth. Supported by a recent IMF study which ranks banking regulation and supervision 'poor' or 'below-average' in four out of the five countries under study, we attribute the limited effectiveness of their banks to government intervention in credit allocation and pricing. Our results cast doubt on the banks' ability to facilitate an economic recovery, and suggest that a monetary policy focused on bank credit alone may not be successful.